The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1007/s11605-011-1561-3
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Management of Hemorrhage from Visceral Artery Pseudoaneurysms after Pancreatic Surgery

Abstract: Endovascular intervention represents the first-line treatment for hemorrhage from pseudoaneurysms after pancreatic surgery. Endovascular embolization or stent-graft placement should be selected individually depending on the involved artery and its vascular anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 36 publications
3
49
0
2
Order By: Relevance
“…Conversely, pseudoaneurysms must be immediately treated as the rupture rate is much greater than true aneurysms (76.3% versus 3.1%) [11,17]. Endovascular management is safe and effective, including fewer complications, shorter hospital stay and recovery [4,18,19]. There are various methods for endovascular treatment, including the placement of coils, stent implantation, injection of polyvinyl alcohol particles, gelfoam or glue, and endoluminal thrombin injection [4,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, pseudoaneurysms must be immediately treated as the rupture rate is much greater than true aneurysms (76.3% versus 3.1%) [11,17]. Endovascular management is safe and effective, including fewer complications, shorter hospital stay and recovery [4,18,19]. There are various methods for endovascular treatment, including the placement of coils, stent implantation, injection of polyvinyl alcohol particles, gelfoam or glue, and endoluminal thrombin injection [4,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Pseudoaneurysms are the most severe concern with regard to post-pancreatoduodenectomy bleeding, occurring in approximately 3.2e4.6% of cases [5,6]. Often arising in the setting of pancreatic fistula, inflammation and irritation of the vasa vasorum leads to weakness in the visceral arterial walls.…”
Section: Discussionmentioning
confidence: 99%
“…In the postoperative patient, bleeding from the gastrointestinal tract or surgical drain is the most common presentation [7]. As many as fortyfive percent of pseudoanuerysms may present with a sentinel bleed [5], which often times goes unrecognized. One institutional study reported a median time of occurrence of twenty-two days postoperatively, though later presentations have been reported as well [7].…”
Section: Discussionmentioning
confidence: 99%
“…The aneurysms can be treated through endovascular techniques or by surgery [8]. Treatment depends on the presentation, location, and size of the aneurysm.…”
Section: Discussionmentioning
confidence: 99%